ANALISIS PENGARUH EARNING PER SHARE DAN RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN : (Studi Kasus Pada PT Astra International Tbk Tahun 2015-2019) - Wibowo, Dedi; Agustina , Risma Citra; Simamora , Saur Cotanius (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
This study aims to determine the effect of earnings per share and return on equity on company value. The sample in this study was PT Astra International Tbk in 2015-2019. This study used secondary data in the form of financial statements obtained from the www.idx.co.id website and the PT Astra International Tbk website. The analysis methods used are multiple linear regression analysis and data analysis using SPSS software version 25. The results of the study partially show that earnings per share have a significant effect on company value with significance 0,002 < 0,05, while return on equity does not have a significant effect on Company Value. The results of the study simultaneously show that earnings per share and return on equity affect the company's value by significance 0,006 < 0,05. Keywords: Earning Per Share (EPS), Return On Equity (ROE), Nilai Perusahaan.